1961
DOI: 10.1002/ange.19610730602
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxymethylene

Abstract: A. EinleitungSchon in der 1. Mitteilungls) iiber hochpolymere Verbindungen hat H. Staudinger**) die l i n e a r e K e t t e n s t ru k t u r

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…Generally, for all POM samples, one broad peak for all degradation products can be observed, while for POM/HAp nanocomposites shape of peaks suggests two or . Additionally, the formic acid can be oxidized to water and carbon dioxide [8,37,38]. The limited amount of methanol (CH 3 OH) may be related to the acidolysis and hydrolysis [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, for all POM samples, one broad peak for all degradation products can be observed, while for POM/HAp nanocomposites shape of peaks suggests two or . Additionally, the formic acid can be oxidized to water and carbon dioxide [8,37,38]. The limited amount of methanol (CH 3 OH) may be related to the acidolysis and hydrolysis [36].…”
Section: Resultsmentioning
confidence: 99%
“…The limited amount of methanol (CH 3 OH) may be related to the acidolysis and hydrolysis [36]. Peak m/z 44 could also correspond to carbonyl, carboxyl or hydroperoxide groups formed in the main chain during thermooxidative degradation [8,37,39] which can induce chain scission followed by the formation of formaldehyde, but they can also oxidize the latter to formic acid. The both reactions are responsible for acidolytic degradation of the polyacetal chain [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the formation of 3 we concluded that in the case of the BF 3 ·OEt 2 -promoted CROP, activation preferably occurs without co-initiator. BF 3 -promoted polymerisation of cyclic acetals without any co-initiator has been reported for polar solvents like nitrobenzene or dichloroethane [Higashimura et al 1965, Kern et al 1961, Kern and Jaacks 1960.…”
Section: H Nmr Spectroscopic Studies Of the Course Of Polymerisationmentioning
confidence: 99%
“…A review of the historical development of polyoxymethylenes is given in [42][43][44]. Comprehensive summaries of the homopolymerization and copolymerization of trioxane can be found in [45][46][47].…”
Section: Polymerization Of Formaldehyde and Trioxanementioning
confidence: 99%